Identitas Gaya Hidup dan Budaya Konsumen dalam Mengkonsumsi Brand The Executive - Rafa'al, Mubaddilah (Jurnal Komunikasi Profesional, 2017)
Humans not only buy the needed goods, but also the brand. Brand goods are self-pride. Buying reputable brands creates a feeling of "more" in the user. With shopping, consumers not only consume the material value or utility value of the goods they buy, but also what the goods indicate. This research departs from J. Baudrillard's thoughts on consumption trends and cultural signs. Researchers use ads from The Executive products. This product is then not only for formal wear, but also for other types of clothing until now become a lifestyle brand.Keywords: Identity, Culture, Consumption